ALK‐rearranged Mesenchymal Neoplasms: A Report of 9 cases Further Expanding the Clinicopathologic Spectrum of Emerging Kinase Fusion Positive Group of Tumors. Issue 2 (7th October 2022) - Dermawan, Josephine K.; DiNapoli, Sara E.; Mullaney, Kerry A.; Sukhadia, Purvil; Agaram, Narasimhan P.; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract: Anaplastic lymphoma kinase (ALK) fusions are oncogenic drivers in diverse cancer types. Although well established in inflammatory myofibroblastic tumor (IMT) and epithelioid fibrous histiocytoma (EFH), ALK rearrangements also occur in the emerging family of kinase fusion‐positive mesenchymal neoplasms. We investigated 9 ALK‐rearranged mesenchymal neoplasms (exclusive of IMT and EFH) arising in 6 males and 3 females with a wide age range of 10 to 78 years old (median 42 years). Tumors involved superficial and deep soft tissue (6) and viscera (3). Three were myxoid or collagenous low‐grade paucicellular tumors with haphazardly arranged spindled cells. Three were cellular tumors with spindled cells in intersecting short fascicles or solid sheets. Three cases consisted of uniform epithelioid cells arranged in nests or solid sheets, with prominent mitotic activity and necrosis. Band‐like stromal hyalinization was present in 6 cases. All tumors expressed ALK; four were positive for S100 and five were positive for CD34, while all were negative for SOX10. By targeted RNA sequencing, the breakpoints involved ALK exon 20; the 5′ partners included KLC1, EML4, DCTN1, PLEKHH2, TIMP3, HMBOX1, and FMR1 . All but two patients presented with localized disease. One patient had distant lung metastases; another had diffuse pleural involvement. Of the six cases with treatment information, five were surgically excised [one also received neoadjuvant radiation therapy (RT)], and one received RT and an ALK inhibitor. Of the four patients with follow‐up (median 5.5 months), one remained alive with stable disease and three were alive without disease. We expand the clinicopathologic spectrum of ALK ‐fused mesenchymal neoplasms, including a low‐grade malignant peripheral nerve sheath tumor‐like subset and another subset characterized by epithelioid and high‐grade morphology.